Vpliv dispergirnega sredstva in veziva na lastnosti zaslonov s P-43 - Županc Mežnar, Lea (Kovine zlitine tehnologije, 1995)
Screens for miniature cathode ray tubes with low-potential excitation of 2-5 kV were deposited by centrifugal settling method. We used phosphor P-43 (Gdsub2Osub2S:Tb) with 1,2 mum average particle size. Suspension was stabilized with the surface active agent and this enabled the preparation of screens with homogenous light output. An optimum amount of binder was empirically determined by preparing and testing a lot of screens. Screen resolution and luminous efficency were 15 mum and 23 lm/W, respectively.
Keywords: Electronika; elektronika; elektronke; zasloni; tanke plasti